The existence of the surface with edge in Minkowsky space with the given Grassman image - Marina Grechneva; Polina Stegantseva (Pracì Mìžnarodnogo Geometričnogo Centru, 2018)
One considers the problem connected with the finding of the non-isotropic surface in Minkowsky space with the help of its Grassman image in the global aspect. This problem can be reduced to the proof of the existence of the solution of the partial differential equation of the second order. The paper deals with the hyperbolic case. One describes the technique of the specialization of the moving frame of the surface. This technique is based on the metric properties of Minkowsky space.